The family member accompanying adult patients in the hospital context. - Espirito Santo, Fatima Helena; Aquino, Alessandra Cristina Oliveira; Chibante, Carla Lube; Santos, Thayane Dias (Investigación y Educación en Enfermería, 2013)
<!-- [if gte mso 9]> <![endif]--> Objective. To identify the actions of family members who accompany adult hospitalized patients and to describe the nursing team’s role regarding that person. Methodology. In this qualitative, descriptive and exploratory research, a questionnaire was applied to 30 nursing team members at a teaching hospital located in the State of Rio de Janeiro, using open questions. To interpret the answers, thematic analysis was applied to categorize the identified qualitative variables. Results. Eighty-nine percent of the participants were female. When analyzing the information contained in the answers to the questionnaire, two types of actions were found: the actions the companion can perform for his/her relative and the actions the nursing team needs to perform. In each action, the following categories were verified: affective dimension, practical dimension, moral dimension and inclusion of the family in care. According to the nursing team, the companion plays a very important role in emotional support and help with the patient’s basic hygiene, although this care should be offered under nursing orientation. Conclusion. Family companions and nursing team members work together to improve the quality of patient care, with positive reflections for their integration in hospital care, which will enhance its continuity in the home-care context.